Movement Analysis Short Pass and Student Palembang 52 State Futsal Team - Hidayatullah, Firdaus; Junaidi, Ilham Arvan (Yayasan Sembilan Pemuda Indonesia, 2023)
This research is to find out if there is an effect of training short passes and zig-zag run to improve the skills of passing the ball by students of the men’s futsal team at SMP Negeri 52 Palembang. The method in this research is descriptive qualitative. The research subjects were students who were included in the men’s futsal team, which consisted of 25 male members, while the object of agility research was the attitude of executing movements short pass and zig-zag run. Data analysis was used for data collection using tests short passes from Arsil, namely the test of kicking the ball from a few minutes to place and target in the fastest time. For the Zig-zag run use the sheet technique observation (checklist). Based on the research results, 7 people got a combined score between record time and target accuracy at intervals of > 124 with a score classification of “very good”. Then there are as many as 16 people getting a combined score at a value interval of 104 - 123 with a “good” score classification. The remaining 2 people get a combined score in the interval 85 - 103 with a “moderate” score classification. Based on the results of the research and discussion it can be concluded that the ability short pass most of them was good, as many as 7 people got scores in the very good category (28%) and as many as 16 people (64%) were included in the good category, and 2 people were included in the medium category (2%). Whereas zig-zag run experienced an increase in agility as indicated by the final result of 79.5% which was classified as good, consisting of 11 students (27.3%) which were categorized as very well, 9 students (50.0%) which were classified as good, 3 students (13.6%) which were categorized as sufficient, and 2 students (9.1%) were categorized as lacking.